Efficiency of oil companies in Russia in the context of energy and sustainable development. (November 2020) - Filimonova, I.V.; Komarova, A.V.; Provornaya, I.V.; Dzyuba, Y.A.; Link, A.E.
Abstract: The transformation of the energy market and the development of its technologies radically change the industry and uncover new segments for competition. Scientific and technological progress is gradually changing the market structure and replacing petroleum products with other energy sources, creating new consumption sectors. However, the oil and gas industry still plays a major role in the energy and fuel balance of the world (almost 60% of global energy consumption is concentrated in the oil and gas sector). Due to the specifics of the petroleum sector, the companies tend to be large and have a significant direct and indirect influence on the oil industry as a whole. In this article, the authors of the study compared Russian and international companies in the oil and gas sector and identified the distinctive features of each group. To reveal the main factors influencing financial performance, we construct models of the dependence of net profit on various macroeconomic, microeconomic, institutional, and additional factors. The basic panel data model is tested, taking into account fixed and random individual effects. Results show that the profit of each major oil and gas company is affected by revenue, production costs, and tax deductions. The key interest rate set by the Central Bank of Russia is also important for the activities of oil and gas companies. A distinctive factor for petroleum corporations is the negative impact of financial leverage on the profits of domestic companies and the negative impact of investment in the environmental area for foreign companies. According to our forecasts, the total profit of the eight largest oil producers in Russia will decrease by 60% in 2020. Such forecasts are not very encouraging, but due to the current market situation, they are not surprising.